Preliminary Study on the Determination of Volcanic Tremor Epicenter Using Semblance Method (Case Study of Sakurajima Volcano) - Ratri Andinisari; Sukir Maryanto; Ahmad Nadhir (Natural B, Journal of Health and Environmental Sciences, 2013)
Volcanic tremor is one of the most important volcanic activities due its strong connection to magma movement and impeding eruption. Therefore, the determination of volcanic tremor epicenter becomes very important. The absence of apparent P and S wave arrival of volcanic tremor is the main constraint of its epicenter determination. The use of semblance method is required because semblance method requires no information about P and S wave arrival in epicenter determination. A preliminary application of semblance method has been done to determine the epicenter of 100 s length volcanic tremor of Sakurajima volcano. In this research we use the recorded seismic signal from 5 different volcano observatories, which are KOM, KAB, HIK, ARI, and HAR. The recorded tremor signal is then analyzed by using semblance method. The analysis is carried out by calculated semblance coefficient in every 30 s moving window along the signal. The resulting semblance coefficient varied from 0,25 to 0,42. The epicenter of observed volcanic tremor is located in the north-east part of Minamidake crater by -18,66o to 54,10o of azimuth counted from the east, while the epicentral distance of the observed volcanic tremor varied from 608,28 to 948,68 m from Minamidake crater.